Help-seeking for genitourinary symptoms: a mixed methods study from Britain's Third National Survey of Sexual Attitudes and Lifestyles (Natsal-3). Issue 10 (30th October 2019) - Mapp, Fiona; Wellings, Kaye; Mercer, Catherine H; Mitchell, Kirstin; Tanton, Clare; Clifton, Soazig; Datta, Jessica; Field, Nigel; Palmer, Melissa J; Hickson, Ford
Abstract : Objectives: Quantify non-attendance at sexual health clinics and explore help-seeking strategies for genitourinary symptoms. Design: Sequential mixed methods using survey data and semistructured interviews. Setting: General population in Britain. Participants: 1403 participants (1182 women) from Britain's Third National Survey of Sexual Attitudes and Lifestyles (Natsal-3; undertaken 2010–2012), aged 16–44 years who experienced specific genitourinary symptoms (past 4 weeks), of whom 27 (16 women) who reported they had never attended a sexual health clinic also participated in semistructured interviews, conducted May 2014–March 2015. Primary and secondary outcome measures: From survey data, non-attendance at sexual health clinic (past year) and preferred service for STI care; semistructured interview domains were STI social representations, symptom experiences, help-seeking responses and STI stigma. Results: Most women (85.9% (95% CI 83.7 to 87.9)) and men (87.6% (95% CI 82.3 to 91.5)) who reported genitourinary symptoms in Natsal-3 had not attended a sexual health clinic in the past year. Around half of these participants cited general practice (GP) as their preferred hypothetical service for STI care (women: 58.5% (95% CI 55.2% to 61.6%); men: 54.3% (95% CI 47.1% to 61.3%)). Semistructured interviews elucidated four main responses to symptoms: not seeking healthcare, seeking information to self-diagnose and self-treat, seeking care at non-specialist services and seeking care at sexual health clinics. Collectively, responses suggested individuals sought to gain control over their symptoms, and they prioritised emotional reassurance over accessing medical expertise. Integrating survey and interview data strengthened the evidence that participants preferred their general practitioner for STI care and extended understanding of help-seeking strategies. Conclusions: Help-seeking is important to access appropriate healthcare for genitourinary symptoms. Most participants did not attend a sexual health clinic but sought help from other sources. This study supports current service provision options in Britain, facilitating individual autonomy about where to seek help.